Bottling, Labeling and Selling Honey in Florida - Nancy Gentry; James D. Ellis (EDIS)
In 2011, the Florida Legislature enacted HB 7209 allowing individuals to manufacture, sell, and store certain types of “cottage foods” (including honey) in an unlicensed kitchen. “Cottage food operations,” as they are called, require no licensing or permitting from the Florida Department of Agriculture and Consumer Services and are not inspected by any other state government entity. This revised 4-page fact sheet was written by Nancy Gentry and James D. Ellis, and published by the UF Department of Entomology and Nematology, August 2012.